Antipsychotic Use and the Risk of Rhabdomyolysis. (October 2014) - Packard, Kathleen; Price, Paul; Hanson, Ashley
Rhabdomyolysis is not a well-understood adverse effect of antipsychotic use. Proposed mechanisms suggest involvement of serotoninergic and/or dopaminergic blockade. The purpose of this study was to describe the relationship between antipsychotic use and rhabdomyolysis. Patients admitted with rhabdomyolysis and taking an antipsychotic from January 2009 to October 2011 were included. Background demographics, laboratory data, medical and physical history, concomitant medications, and hospital course data were collected. Of the 673 cases admitted with rhabdomyolysis, 71 (10.5%) were on an antipsychotic. This is significantly greater when compared to the general US population, where only 1.3% of individuals take an antipsychotic drug ( P < .0001). Cause of rhabdomyolysis was not documented in 38% of cases, and antipsychotic use was suspected in 10% of cases. No significant correlations were found between antipsychotic type and other patient-specific parameters. Seventeen (25%) of these patients were taking 2 or more antipsychotics. The largest percentage was on quetiapine (Seroquel ® ; AstraZeneca, Wilmington, Delaware), the most commonly prescribed antipsychotic in the United States. Antipsychotic use is a risk factor for rhabdomyolysis and seems to be more common in those taking multiple agents. More research needs to be done to determine which antipsychotics have a higher risk and which receptors are involved. Providers should be aware of rhabdomyolysis associated with antipsychotic use.